The marginal house as the imaginary space/nation - Molina-Espinoza, Ileana (2023)
The concept of nation is indispensable for every individual and people. It is what creates a sense of belonging and cultural and national identity. In hernovel The house on Mango Street, Chicana writer Sandra Cisneros explores the construction of this space through the metaphor of the house. In this text, the protagonist Esperanza Cordero transforms the space of her marginal home into the equivalent of her nation, thus building a kind of imaginary country where she can take root and grow.